Social project appraisal and environmental impact assessment : a necessary but complicated theoretical bridge. - Azqueta, Diego (1992)
Discusses two issues which must be considered when incorporating environmental values in the framework of social project appraisal. These are: (1) there is an important theoretical gap between the two sides of the equation that need to be linked together : social project appraisal and environmental impact assessment have very different theoretical backgrounds; (2) if environmental impact assessment is to be introduced properly into social project appraisal, it will require the modification of some major accounting prices.